'Back to work'—factors facilitating migrants' re-entry into their previous vocations. Issue 8 (17th November 2022) - Eliasson, Eva; Teräs, Marianne; Osman, Ali
ABSTRACT: This article focuses on 'successful migrants', who have succeeded in gaining employment in Sweden in their previous vocational area. The aim is to describe factors on various levels – individual, organisational and national – that have facilitated migrants' way back to work as well as their inclusion at workplaces. Twenty migrants and five employers/mentors were interviewed. The overarching theme of facilitating factors concerns language proficiency, individual factors, enabling frameworks, and supporting persons and networks. The migrants' own ambitions and motivations, and the support they got in interpersonal encounters were especially emphasised as important. In the migrants' narratives, a central theme in relation to the theoretical perspective was how to deal with threats to their social and professional identity in the new country. For them, maintaining a positive self-image was key to the strength needed to fight for a return to working life. People in the environment were important in this struggle – for positioning them as competent persons and for offering support.